Spider web - Fowler, Earlene (Fowler, Earlene. Benni Harper mysteries., 2011)
The Memory Festival is a celebration of recollections and loved ones through crafts. But when a local cop is wounded by a mysterious sharpshooter who seems to have a vendetta against the police, Benni fears for "her" loved ones, especially her police chief husband.